Skandalista Julian Tuwim - Łuszczykiewicz, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article attempts to argue that Tuwim’s personality and work can be explained by looking into his early childhood and writing. It is definitely the period inadequately explored by critics. The author discusses key moments in the poet’s biography and most crucial elements of his work, paying particular attention to controversies triggered by some texts and themes in his writing. The article also focuses on the analysis of conflicts that Tuwim suffered from in his life. Tuwim’s strategy of provocation is also taken under scrutiny. The article presents Tuwim’s poetry as a lasting contribution to Polish literature and as a body of work which manages to resist ideological readings.